2011
DOI: 10.1152/ajpregu.00057.2011
|View full text |Cite
|
Sign up to set email alerts
|

Calorie restriction attenuates LPS-induced sickness behavior and shifts hypothalamic signaling pathways to an anti-inflammatory bias

Abstract: MacDonald L, Radler M, Paolini AG, Kent S. Calorie restriction attenuates LPS-induced sickness behavior and shifts hypothalamic signaling pathways to an anti-inflammatory bias. Am J Physiol Regul Integr Comp Physiol 301: R172-R184, 2011. First published April 27, 2011 doi:10.1152/ajpregu.00057.2011 has been demonstrated to alter cytokine levels; however, its potential to modify sickness behavior (fever, anorexia, cachexia) has not. The effect of CR on sickness behavior was examined in male C57BL/6J mice fed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 82 publications
(141 reference statements)
2
52
0
Order By: Relevance
“…Therefore, at least some of the reversible obesity-induced changes in reward behaviors could be due to changes in inflammatory signaling in brain areas controlling reward functions. Such changes have been shown in the hypothalamus (47,71), hippocampus (9,81), and striatum (41,49). It will be interesting to examine such changes in inflammatory signaling in other key structures controlling reward functions, such as the nucleus accumbens, ventral tegmental area, and orbitofrontal cortex.…”
Section: Perspectives and Significancementioning
confidence: 95%
“…Therefore, at least some of the reversible obesity-induced changes in reward behaviors could be due to changes in inflammatory signaling in brain areas controlling reward functions. Such changes have been shown in the hypothalamus (47,71), hippocampus (9,81), and striatum (41,49). It will be interesting to examine such changes in inflammatory signaling in other key structures controlling reward functions, such as the nucleus accumbens, ventral tegmental area, and orbitofrontal cortex.…”
Section: Perspectives and Significancementioning
confidence: 95%
“…Williams et al (1997) similarly reported depressed feed intake in pigs reared in poor sanitary conditions when compared with those reared in good sanitary conditions. Infection-induced anorexia has been considered as part of the host non-specific immune response, which consists in reducing the availability of nutrients essential to development and growth of pathogens (Exton, 1997;MacDonald et al, 2011). In addition, anorexia seems to enhance function and proliferation of macrophages, contributing to recognition and elimination of pathogens (Exton, 1997).…”
Section: Voluntary Feed Intake and Growth Performancementioning
confidence: 99%
“…To the best of our knowledge, designer receptors exclusively activated by designer drug has been seldom used to investigate inflammatory anorexia (42). A unique advantage of this technique is that it allows for robust stimulation of feeding without the need for fasting of animals, which can interfere with immunity and the endocrine axis (43)(44)(45). Moreover, each mouse can be used as its own control.…”
Section: Pharmacogenetics and Brain Surgerymentioning
confidence: 99%